Amorphous carbon nitrogenated films prepared by plasma immersion ion implantation and deposition - Rangel, Elidiane C.; Durrant, Steven F.; Rangel, Rita C. C.; Kayama, Milton E.; Landers, Richard; da Cruz, Nilson C. (Elsevier B.V., 2006)
In this work, an investigation was conducted on amorphous hydrogenated-nitrogenated carbon films prepared by plasma immersion ion implantation and deposition. Glow discharge was excited by radiofrequency power (13.56 MHz, 40 W) whereas the substrate-holder was biased with 25 kV negative pulses. The films were deposited from benzene, nitrogen and argon mixtures. The proportion of nitrogen in the chamber feed (R-N) was varied against that of argon, while keeping the total pressure constant (1.3 Pa). From infrared reflectance-absorbance spectroscopy it was observed that the molecular structure of the benzene is not preserved in the film. Nitrogen was incorporated from the plasma while oxygen arose as a contaminant. X-ray photoelectron spectroscopy revealed that N/C and O/C atomic ratios change slightly with R-N. Water wettability decreased as the proportion of N in the gas phase increased while surface toughness underwent just small changes. Nanoindentation measurements showed that film deposition by means of ion bombardment was beneficial to the mechanical properties of the film-substrate interface. The intensity of the modifications correlates well with the degree of ion bombardment. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: plasma immersion ion implantation and deposition; mechanical properties; wettability; roughness